The Diachronic Perspective on the Morphology of Compound Adjectives - Gavranović, Valentina; Prodanović, Marijana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
This paper focuses on a diachronic study of compound adjectives found in the Old and Middle English texts of the Helsinki Corpus. The compound adjectives of both periods are analysed, and further classified into types on the basis of the word class their constituent elements belong to. The aim of the research is to follow the development courses of compound adjective types in the two language periods and to investigate what happened to them in Modern English. The comparison of the types results in the description of the character of these changes, illuminating which Old English types survived into the subsequent periods, which were lost from the language, and what were the new ones introduced in the Middle English period.